OPTIMALISASI PENDAPATAN PETANI CABAI MERAH DENGAN DIVERSIFIKASI USAHATANI - Benidzar M. Andrie; Ane Novianty (Universitas Galuh Ciamis, 2021)
Intercropping is one way to increase land use efficiency by planting several types of plants on the same land at the same time. Planting that is arranged in such a way in plant rows will help efforts to achieve the production potential of the two types of intercropped plants. This study aims to determine the amount of revenue, income, and eligibility in Bojonggambir District. The research method used was a survey on farmers who carried out farming with continuous red chili crop diversification. The results of this study with a land area of 0.34 indicate that the income of farmers is Rp. 9,590,000.00, with a total cost of Rp. 3,699,000 so that you get an income of Rp. 5,891,000 for six months, for eligibility as seen from the RC ratio value of 2.6 and for the Break Even Point (BEP) Unit of 51.90 kg, BEP (Rp) Rp. 578,246 and BEP (Selling Price) Rp. 3,111 / kg with a total production of 858.25 kg of the total production means that this business is financially feasible